The beneficiation of lithium minerals from hard rock ores: A review - Tadesse, Bogale; Makuei, Fidele; Albijanic, Boris; Dyer, Laurence (Minerals engineering, 2019)
•Beneficiation methods of lithium minerals from hard rock ores were reviewed.•Spodumene is currently the main source of lithium from ores.•Flotation, DMS and magnetic separation are the main beneficiation methods.•Similarities between lithium minerals and gangue makes beneficiation complicated.•Significant research in lithium minerals other than spodumene is needed. The demand for lithium minerals has increased considerably in recent years due to the application of lithium compounds in lithium ion battery technology, portable electronic gadgets and power storage systems. Spodumene is the main lithium bearing mineral which is currently being explored and processed due to its high lithium content and the extensive occurrence of deposits. This literature review focuses on the various techniques used in the beneficiation of lithium minerals from hard rock pegmatite ores. Dense media separation and flotation are the main beneficiation methods used for the separation of lithium minerals from ores. The close similarity in chemical and physical properties between lithium minerals and associated gangue minerals complicates the beneficiation of lithium minerals from ores. Surface chemistry of minerals, type of collector, pulp pH, chemical pre-treatment methods, and the presence of slimes play key roles in lithium minerals flotation. This review also deals with the beneficiation flowsheets employed at some of the larger lithium processing plants in the world. Spodumene from pegmatite deposits is expected to be the main source of lithium from ores at present although future sources would most probably include other minerals such as lepidolite, petalite, zinnwaldite, jadarite and hectorite.